2016
DOI: 10.5296/jei.v2i2.10217
|View full text |Cite
|
Sign up to set email alerts
|

Design Factors Affect User Experience for Different Cultural Populations

Abstract: <p>With increasing changes in our demographic populations and new immigrants settling in the US, there is an increasing need for visual communications that address the diversity of our populations. This paper draws from the results of the researcher’s several past research and teaching projects that worked with different cultural populations. These projects examined the theme of multicultural design with a particular focus on user experience for audiences from different cultural backgrounds. The nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…This is because cross-cultural designs highlighted the uniqueness of designs characterized by local identity. Local identity in designs needed to be created in order to be accepted by public and industries (Chu, 2016). Therefore, the design should be able to elevate the popularity of local culture in the eyes of the world.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because cross-cultural designs highlighted the uniqueness of designs characterized by local identity. Local identity in designs needed to be created in order to be accepted by public and industries (Chu, 2016). Therefore, the design should be able to elevate the popularity of local culture in the eyes of the world.…”
Section: Resultsmentioning
confidence: 99%
“…Needs analysis can be implemented using qualitative or quantitative approach by using suitable instruments including interviews or questionnaires (Chu, 2016). This study applied a qualitative approach to identify cross-cultural needs in the context of teaching and learning, especially to generate corporate identity design.…”
Section: Methodsmentioning
confidence: 99%
“…La experiencia del usuario UX se refiere a "la experiencia que un individuo obtiene cuando interactúa con un producto en entornos o situaciones particulares sujetos a determinadas condiciones que rigen el sistema, que pueden afectarla", (36) destacando aspectos relevantes como la belleza, la diversión, el placer y el crecimiento personal que satisfacen las necesidades humanas mediante la interacción con el producto, este aspecto es tan importante que múltiples organizaciones se han comprometido con mejorar la experiencia del usuario en la Web, la cual implica considerar a los usuarios y sus diferentes características y capacidades dentro del amplio abanico de perfiles de usuario Web que propone la diversidad humana, (37) esta misma diversidad se refleja principalmente en proyectos con públicos objetivo que provienen de diferentes orígenes culturales, donde se deben de tomar múltiples variables extras como las que cita Chu, (38) que sugiere múltiples maneras de evitar el diseño culturalmente insensible, las cuales van desde el análisis de valores culturales consultando a expertos locales, y la creación de paquetes de localización que incluya las preferencias del público objetivo para colores, símbolos, normas sociales y lenguajes bidireccionales.…”
Section: User Experience Ux (Experiencia De Usuario)unclassified
“…Based on this, the web designer has properly managed the visual elements in the web page, and found that the increase in visual intensity between the user experience and the visual impact can attract users 7 . By adjusting the visual elements of the web interface, a user-guided effect is achieved 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%